2018
DOI: 10.1007/s00464-018-6273-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative carbohydrate loading on intraoperative body temperature: a randomized controlled clinical trial

Abstract: CHO had no effect on raising the intraoperative core temperature, and no negative impact on the perioperative outcome. CHO prevented the loss of lower limb muscle mass, which may lead to better postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Adequate energy is the material basis of and an inherent condition for muscle contraction, supporting the finding that oral carbohydrates promote uterine contractility and reduce vaginal bleeding. 19,20 Preoperative oral carbohydrate consumption reduces postoperative muscle loss, promotes muscle strength, 21 and facilitates early physical activities (out of bed). We recommend administering patient-controlled analgesia before the patient gets out of bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate energy is the material basis of and an inherent condition for muscle contraction, supporting the finding that oral carbohydrates promote uterine contractility and reduce vaginal bleeding. 19,20 Preoperative oral carbohydrate consumption reduces postoperative muscle loss, promotes muscle strength, 21 and facilitates early physical activities (out of bed). We recommend administering patient-controlled analgesia before the patient gets out of bed.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative oral carbohydrate consumption reduces postoperative muscle loss, promotes muscle strength, 21 and facilitates early physical activities (out of bed). We recommend administering patient‐controlled analgesia before the patient gets out of bed.…”
Section: Discussionmentioning
confidence: 99%
“…The carbohydrate drinks before surgery improve carbohydrate uptake, utilization, storage, and protein metabolism with a 50% reduction in loss of lean body mass [ 50 ]. Preoperative carbohydrate beverages help to store glycogen in the muscle [ 13 ] and prevent the loss of lower limb mass leading to better postoperative recovery [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac patients, the use of ERAS protocol results in a 35% reduction in postoperative insulin doses [ 17 ]. The preoperative carbohydrate loading reduces the expression of Human leukocyte antigen (HLA)-DR on monocytes which decreases the risk of postoperative infection [ 18 ] and reduces the intraoperative core body temperature [ 19 ]. In addition, it improves muscle function because of less post-operative protein and nitrogen loss [ 20 ], which facilitates wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…It is also of interest to weigh the possible risks against the suggested benefits of preoperative carbohydrate consumption, namely attenuation of insulin resistance and lesser catabolism of lean body tissues in response to fasting and stress during and immediately after surgery. We want to highlight the following 2 important points: first, studies that measured and showed a possible benefit in postoperative glycemic control, insulin resistance, and body composition changes with preoperative carbohydrate loading come mostly from lean patients and patients with cancer; and consideration should be given that the absolute amount of lean mass-sparing through preoperative carbohydrate loading was recently measured to be ,.5 kg in nonobese patients undergoing laparoscopic colon cancer surgery [10]. Also, it is well known that the contribution of lean mass to total weight loss is inversely proportional to the initial degree of adiposity [11], making acute lean tissue wasting far less concerning in patients with obesity compared with patients with healthy weight or underweight.…”
Section: Surgery For Obesity and Related Diseases 16 (2020) E5-e7mentioning
confidence: 99%